Cryptic diversity, geographical endemism and allopolyploidy in NE Pacific seaweeds. Issue 1 (December 2017) - Neiva, João; Serrão, Ester; Anderson, Laura; Raimondi, Peter; Martins, Neusa; Gouveia, Licínia; Paulino, Cristina; Coelho, Nelson; Miller, Kathy; Reed, Daniel; Ladah, Lydia; Pearson, Gareth
Abstract Background Molecular markers are revealing a much more diverse and evolutionarily complex picture of marine biodiversity than previously anticipated. Cryptic and/or endemic marine species are continually being found throughout the world oceans, predominantly in inconspicuous tropical groups but also in larger, canopy-forming taxa from well studied temperate regions. Interspecific hybridization has also been found to be prevalent in many marine groups, for instance within dense congeneric assemblages, with introgressive gene-flow being the most common outcome. Here, using a congeneric phylogeographic approach, we investigated two monotypic and geographically complementary sister genera of north-east Pacific intertidal seaweeds (Hesperophycus andPelvetiopsis ), for which preliminary molecular tests revealed unexpected conflicts consistent with unrecognized cryptic diversity and hybridization. Results The three recovered mtDNA clades did not match a priori species delimitations.H. californicus was congruent, whereas widespreadP. limitata encompassed two additional narrow-endemic species from California -P. arborescens (here genetically confirmed) andP. hybrida sp. nov. The congruence between the genotypic clusters and the mtDNA clades was absolute. Fixed heterozygosity was apparent in a high proportion of loci inP. limitata andP. hybrida, with genetic analyses showing that the latter was composed of bothH. californicus andP. arborescens genomes. All four inferred species could be distinguished based on their general morphology. Conclusions This study confirmed additional diversity and reticulation within NE PacificHesperophycus /Pelvetiopsis, including the validity of the much endangered, modern climatic relictP. arborescens, and the identification of a new, stable allopolyploid species (P. hybrida ) with clearly discernable ancestry (♀H. californicus x ♂P. arborescens ), morphology, and geographical distribution. Allopolyploid speciation is otherwise completely unknown in brown seaweeds, and its unique occurrence within this genus (P. limitata possibly representing a second example) remains enigmatic. The taxonomic separation ofHesperophycus andPelvetiopsis is not supported and the genera should be synonymized; we retain only the latter. The transitional coastline between Point Conception and Monterey Bay represented a diversity hotspot for the genus and the likely sites of extraordinary evolutionary events of allopolyploid speciation at sympatric range contact zones. This study pinpoints how much diversity (and evolutionary processes) potentially remains undiscovered even on a conspicuous seaweed genus from the well-studied Californian intertidal shores let alone in other, less studied marine groups and regions/depths.